2009
DOI: 10.1016/j.ncl.2009.08.005
|View full text |Cite
|
Sign up to set email alerts
|

Hormonal Aspects of Epilepsy

Abstract: Synopsis The interactions between hormones, epilepsy, and the medications used to treat epilepsy are complex, with tridirectional interactions which affect both men and women in various ways. Abnormalities of baseline endocrine status occur more commonly in people with epilepsy, and are most often described for the sex steroid hormone axis. Common symptoms include sexual dysfunction, decreased fertility, premature menopause, and polycystic ovarian syndrome. Antiepileptic drugs and hormones have a bidirectional… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
44
0
17

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 84 publications
(66 citation statements)
references
References 81 publications
(104 reference statements)
1
44
0
17
Order By: Relevance
“…Thyroid hormones have an important role in perinatal development of the central nervous system, and recent studies have reported that the incidence of seizure in people with hyperthyroidism is higher than in individuals with normal hormone levels. 17 Our data show that the frequency of seizure in CH patients was 2.7%. Although no study has shown a correlation between seizure and CH in newborns or children, a recent case report described an infant suffering from intractable neonatal seizures with CH.…”
Section: Discussionmentioning
confidence: 51%
“…Thyroid hormones have an important role in perinatal development of the central nervous system, and recent studies have reported that the incidence of seizure in people with hyperthyroidism is higher than in individuals with normal hormone levels. 17 Our data show that the frequency of seizure in CH patients was 2.7%. Although no study has shown a correlation between seizure and CH in newborns or children, a recent case report described an infant suffering from intractable neonatal seizures with CH.…”
Section: Discussionmentioning
confidence: 51%
“…Finally, brain-derived neurotrophic factor (BDNF) enhances the expression of GS and the glutamate transporter GLAST in astrocytes (Dai et al, 2012). Because stress (Friis and Lund, 1974), estrous cycle hormones (Pennell, 2009), glucose metabolism (Garriga-Canut et al, 2006), and neuronal reorganization (Ben-Ari, 2008) have been implicated in the pathophysiology of seizures and epilepsy, it is possible that perturbations in these factors influence the expression of GS in MTLE. Whether and exactly how these factors regulate GS in MTLE remain to be established.…”
Section: Regulation Of Gs In Astrocytesmentioning
confidence: 99%
“…Oxcarbazepine (OXC) and CBZ may be related to alterations in thyroxin and free thyroxin serum levels, but normal TSH levels. These abnormalities are not clinically significant [26].…”
Section: Carbamazepine and Oxcarbazepinementioning
confidence: 86%
“…Polycystic Ovary Syndrome It is important that clinicians consider the association of PCOS in women treated with VPA, as is associated with metabolic disorders (such as obesity, glucose intolerance, hyperinsulinaemia, and dyslipidaemia) and endometrial carcinoma in the long term [26]. PCOS should be monitored in women with VPA monotheraphy/polytherapy [84].…”
Section: Endocrinologicalmentioning
confidence: 99%